Evaluation of improved Cassava (Manihot esculanta Crantz) varieties in mid land area of South Omo Zone, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
Cassava is one of the most important foods security crops, especially in those regions disposed to difficult crop environments. The crop is also grown in the southern part of Ethiopia and plays an important role for home consumption, animal feed and source of income for small-scale farmers. However, its productivity is still low due to the lack of improved planting materials. Therefore, the experiment was conducted at Jinka Agricultural Research Center’s research site during the 2018 and 2019 consecutive cropping seasons to investigate the adaptability of improved cassava varieties and to select high-yielding variety/varieties for the target area. Four improved cassava varieties (Hawassa-4, Kello, Qulle and Chichu) and one local check were used as treatments and arranged in randomized complete block design with three replications. ANOVA revealed that the interaction between year and variety showed non-significant, whereas varieties performed significantly different (p